2020
DOI: 10.1155/2020/5143013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of TIPS versus BRTO on Bleeding Gastric Varices: A Meta-Analysis

Abstract: Background and Aim. Upper gastrointestinal bleeding is a threat to patients with gastric varices (GVs). Previous studies have concluded that both transjugular intrahepatic portosystemic shunt (TIPS) and balloon-occluded retrograde transvenous obliteration (BRTO) are effective treatments for patients with GV. We aimed to compare the efficiency and outcomes of these two procedures in GV patients through meta-analysis. Methods. The PubMed, Cochrane Library, EMBASE, and Web of Science databases were searched using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Table 4 shows the notable complications after each procedure. Recent meta-analyses[ 45 - 47 ] have concluded that BRTO in patients with GVs bleeding is associated with lower rates of rebleeding and postprocedural hepatic encephalopathy, as well as better survival than TIPS. Although BRTO is effective in eradicating GVs, it is associated with complications such as postprocedural EVs, ectopic varices, and intractable ascites.…”
Section: Advantages Of Brto Over Other Treatmentsmentioning
confidence: 99%
“…Table 4 shows the notable complications after each procedure. Recent meta-analyses[ 45 - 47 ] have concluded that BRTO in patients with GVs bleeding is associated with lower rates of rebleeding and postprocedural hepatic encephalopathy, as well as better survival than TIPS. Although BRTO is effective in eradicating GVs, it is associated with complications such as postprocedural EVs, ectopic varices, and intractable ascites.…”
Section: Advantages Of Brto Over Other Treatmentsmentioning
confidence: 99%
“…They reported a significant difference in overall survival (risk ratio [RR]: 0.81; p ¼ 0.03) and rebleeding rates (RR: 2.61; p ¼ 0.03) between TIPS and BRTO groups. 47 In conclusion, the benefits and complications of TIPS and BRTO complement each other, and recently there has been increased application of combined TIPS-BRTO in the management of GV. Implementing BRTO first provides an advantage of increasing the portal vein diameter, making access to TIPS less challenging.…”
Section: Gastric Varicesmentioning
confidence: 92%
“…58 In a recent meta-analysis, BRTO was also found to be superior to TIPS for fundal GV in terms of higher overall survival rate and lower rebleeding rates. 59 Endoscopic hemospray is another innovation in the management of AVB. TC-325 is a hemostatic powder which adheres to bleeding site and achieves rapid hemostasis when it came into contact with blood or tissue in the gastrointestinal tract.…”
Section: Avbmentioning
confidence: 99%